Primary Risk of Hypertension in Women with Age 45 - 54 Years - Dewi Puspito Sari; Dwi Sutiningsih (Universitas STRADA Indonesia, 2019)
Hypertension is the silent killer, one of the main risk factors for heart attack and stroke. Based on Riskesdas data in 2018 the prevalence of hypertension blood pressure measurements in Indonesia increased by 8.3%, from 25.8% (in 2013) to 34.1% (in 2018). The prevalence of hypertension in Jambi Province based on the results of the 2013 Riskesdas was quite high at 24.6%. In Sarolangun Regency primary hypertension was second only to ARI, which was 16.3%. But the study of the characteristics of patients with primary hypertension in Sarolangun District is still limited. The purpose of this study was to determine the characteristics of patients with primary hypertension, especially the age and sex of patients in Sarolangun District in 2016. The method of this study was an observational descriptive study, with a case control study design. The sampling technique uses total sampling.